TERRAE ULTIMA THULE: COOPERATION IN THE ARTIC REGION (Journal of the Spanish Institute for Strategic Studies, 2018)
The Arctic is a region where some of the world’s greatest superpowerscoexist in relative harmony, even though diplomatic relations betweenmany of them have been tense since the last century. And despite theincreasing number of conflicts in other regions, Arctic cooperationremains stable and solid. How can we explain this? Several factors, suchas the equitable sharing of natural resources under an internationallegal framework, soft-law institutions that enable dialogue and a terrainthat is hostile to all of them alike, have not only created the conditionsnecessary for cooperation, but have also eliminated the possibility ofconflict in this part of the world. This unusual situation has led toa decades-old debate among academia and the public as to whethercooperation will continue in the future.